Test method for mechanical characteristics of combined electrical, thermal and mechanical deterioration of insulating oil-paper
Patent Information
- Application Number
- JP2023222872
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-21
- Filing Date
- 2023-12-28
- Publication Date
- 2025-01-09
- Estimated Expiration
- 2043-12-28
AI Technical Summary
【0017】 本発明は、絶縁油紙の電気·熱·機械複合劣化の機械的特性の試験方法を提供し、コンバータ変圧器絶縁油紙の電気·熱·機械複合劣化条件下での機械的特性を研究するために、以下のマルチ物理フィールド結合の絶縁油紙劣化実験と、分子動力学に基づいた絶縁油紙劣化シミュレーションを実行した。まず、本発明は、劣化後のサンプルの重合度および引張強度を通じて、サンプルの巨視的な機械的特性の劣化状況を分析し、次に、X線回折分光法とSEM走査電子顕微鏡法を使用して、サンプルの機械的特性の劣化の微視的なメカニズムを初歩に分析し、最後に、分子動力学シミュレーションによって得られた絶縁紙セルロースの平均二乗変位、相互作用エネルギー、機械弾性率などの指標と組み合わせることで、絶縁紙の電気·熱·機械複合劣化条件下での機械的特性の劣化メカニズムが明らかにし、絶縁紙の巨視的な機械的特性と微視的な物理·化学的特性の変化の間の関係を構築し、絶縁紙の寿命予測にデータ基盤と理論的サポートを提供し、同時に、変圧器の油紙絶縁の劣化のメカニズムを原子レベルで研究することに効果的な方法を提供した。
Smart Images

Figure 2025003273000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the technical field of deterioration of insulating oil paper, and in particular to a method for testing the mechanical properties of insulating oil paper during combined electrical, thermal and mechanical deterioration. [Background technology]
[0002] The statements in this section merely provide background information related to the present invention and do not necessarily constitute prior art.
[0003] The insulating oil paper of converter transformers will inevitably deteriorate due to mechanical vibrations caused by moisture, oxygen, high temperature, AC and DC electric fields, and DC bias magnetic fields during operation. Due to changes in the microscopic structure, the electrical and mechanical properties of the deteriorated insulating paper will be greatly affected, and it will no longer be able to function as an insulator for high-voltage equipment. In order to realize predictions for the life and service life of insulating paper and ensure the stable operation of the power grid, scholars have proposed many physical and chemical properties of insulating paper as characteristic parameters for the deterioration of insulating paper, such as the degree of polymerization, the dielectric spectrum in the frequency domain, furfural in oil, and new characterization quantities. Among them, the mechanical properties of insulating paper are easy to measure and can more accurately predict the life of insulating paper. However, due to the complex working conditions during the operation of converter transformers, it is difficult to realize online monitoring and short-term inspection of their mechanical performance. Therefore, studying the laws and mechanisms of the deterioration of insulating oil paper with time and the changes in mechanical performance due to conditions is of great significance to the stability and safety of converter transformers.
[0004] The cellulose insulating paper used in converter transformers is a grade A sulfate wood pulp paper mainly composed of α-cellulose, hemicellulose and lignin, the mass fractions of the three are 90%, 6%-7%, and 3%-4%, respectively. α-cellulose forms crystalline and amorphous regions (non-crystalline regions). The crystalline regions have stable physical and chemical properties, uniform crystal grain size distribution, and many amorphous regions, which are prone to glass transition due to temperature changes. The deterioration of cellulose insulating paper is mainly caused by the scission or displacement of the cellulose main chain and the destruction of the orientation sequence between the cellulose chains. The main factors that can cause the deterioration and decomposition of cellulose during the operation of converter transformers include moisture, oxygen, and external stress (such as electric field, high temperature, and mechanical stress). Moisture and oxygen react directly with the functional groups of cellulose polymers, causing decomposition, hydrolysis and oxidative decomposition, respectively, and external stress decomposes cellulose by strengthening the motion of cellulose molecules, changing the polarity of cellulose molecules, stretching cellulose chains, and other methods. Moreover, the effect of external stress is particularly special, and the deterioration of insulating paper due to the three types of stress - electrical stress, thermal stress, and mechanical stress - is not a "1+1" overlay, but rather has a relationship in which they mutually influence, promote, and inhibit each other. Changes in the microscopic structure of cellulose lead to a decline in the macroscopic mechanical properties, electrical properties, and other physical and chemical properties, so by observing the rules and mechanisms by which the mechanical properties of insulating paper change, it is possible to predict the degree of deterioration and lifespan of insulating paper.
[0005] Current research on the degradation of cellulose insulating paper mainly includes the effects of oxygen, moisture, etc. on the decomposition rate of cellulose and the corresponding products, the life model of oil-paper insulation system, the change in the microscopic structure of insulating paper after degradation, the modification of cellulose insulating paper, the multi-field composite degradation simulation of insulating paper using molecular dynamics, etc. The above studies have played an important role in elucidating the performance degradation mechanism of insulating paper and predicting the life of insulation system, but the influence of the composite effect of electric field, thermal field, and mechanical stress field on the mechanical performance degradation of insulating paper has not been comprehensively studied. Since the degradation effect of external stress on insulating paper is mutually influencing, studies that consider only one or both external stresses alone will deviate from the actual results. Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention provides a method for testing the mechanical properties of insulating oil paper under electrical-thermal-mechanical composite aging. First, a platform for testing the electrical-thermal-mechanical composite aging of insulating paper is designed, then the sample is subjected to multi-field composite aging tests under different conditions, and the polymerization degree and tensile strength tests are further performed on the aged sample to obtain the change rules of the mechanical properties of the sample after aging. Then, the causes of the deterioration of the mechanical properties are primarily analyzed in combination with XRD spectrum and microscopic morphology diagram; In order to further explore the microscopic mechanism of the deterioration of the mechanical properties of insulating paper under the action of multi-fields, a molecular dynamics simulation is carried out on the insulating paper under the composite aging of multi-physical fields to establish the relationship between the deterioration of the macroscopic mechanical properties of insulating paper and the changes of the microscopic physical and chemical properties, so as to provide a data basis and theoretical support for the prediction of the life of insulating paper, thereby solving the problems existing in the prior art.
[0007] In order to solve the above technical problems, the present invention is realized through the following technical solutions: The present invention relates to Building an AC and DC, thermal and mechanical stress combined degradation experiment platform to prepare insulating oil-paper samples with different degradation states; Measure the polymerization degree and tensile strength of the insulating oil paper samples in different aging states to obtain the change rule of mechanical performance after aging, and observe the microscopic morphology diagrams and XRD spectra of the insulating oil paper samples in different aging states to analyze the deterioration cause of mechanical performance; constructing cellulose molecular chains and amorphous unit cells, optimizing the structure, and obtaining a cellulose model; Building an oil-paper mixture model by considering the effect of insulating oil on insulating oil-paper; Based on the cellulose model and the oil-paper mixed model, a molecular dynamics simulation is performed on the oil-paper samples in different degradation states to establish a relationship between the degradation of the macroscopic mechanical performance and the changes of the microscopic physical and chemical properties of the insulating oil-paper; This is a test method for the mechanical properties of insulating oil-paper containing fluorine-based insulating paper subjected to combined electrical, thermal and mechanical deterioration.
[0008] Specifically, the purpose of constructing an AC / DC-thermal-mechanical stress combined degradation experiment platform is to: Construct a high temperature degradation box, In order to apply a constant amplitude vibration to the insulating oil paper, a vibration generator was installed on the base of the high-temperature deterioration box. An AC and DC circuit is constructed, and the DC voltage and the AC voltage are respectively supplied by two transformers, and the DC voltage and the AC voltage are jointly applied to the insulating sleeve at the top of the degradation box; It involves putting the pre-treated insulating oil-papers into different aging tanks respectively, and arranging the aging tanks inside an aging box.
[0009] The preparation of insulating oil-paper samples with different deterioration states includes the following: The experimental temperature was 140°C, the electric field strength was 5kV / mm, the AC / DC voltage ratio was 1:1, the mechanical stress vibration frequency was 100Hz, the vibration amplitude was 1mm, and different combinations of the three external factors, namely temperature, electric field, and mechanical field, were applied to the insulating oil paper sample, and an accelerated aging test was performed on the insulating oil paper sample for 0 to 360 hours.
[0010] The polymerization degree of the insulating oil paper samples is measured by a viscosity test method, the cumulative loss rate of cellulose polymerization degree is fitted by a first-order reaction rate equation to obtain the cumulative loss rate of cellulose under the influence of different factors, and a tensile strength test is performed on the insulating oil paper samples with vibration treatment and the insulating oil paper samples without vibration treatment, and the stress-strain relationship curves of the two insulating oil paper samples are drawn to obtain the elastic modulus and tensile strength under the action of different factors.
[0011] The application of AC and DC electric fields has a significant promoting effect on the decrease in the degree of polymerization, and the decrease in the degree of polymerization of the insulating paper after vibration is more significant than that of insulating paper degraded by AC and DC electric fields; that is, vibration is a more significant factor in promoting the decrease in the degree of polymerization of the insulating paper, and the rigidity coefficient of the insulating paper after vibration decreases, making the insulating paper more susceptible to damage; that is, vibration reduces the mechanical properties of the insulating paper, making it more susceptible to decomposition and damage during the degradation process, and ultimately destroying the insulating structure.
[0012] As the degradation time increases, the degradation of the insulating paper cellulose becomes gradually more severe. The reason is that under the action of stress, the molecular forces between the cellulose chains weaken, the arrangement becomes loose, and the cellulose main chains are stretched or broken, resulting in voids and cracks on the surface of the fibers. Under the action of mechanical force, the crystalline phase content of the cellulose crystals decreases, and the flexibility of the molecular chains increases, making them more susceptible to deformation.
[0013] A cellulobiose molecular model was constructed, and two cellulose molecular chains with a degree of polymerization of 10 were constructed using the cellulobiose molecular model as the basic repeating unit, and a density of 1.5 g / cm was obtained using the AC module. 3Construct an amorphous unit cell of and optimize the structure using the Forcite module to obtain a cellulose model.
[0014] Paraffin C in insulating oil 18 H 38 , Cycloalkane C 18 H 32 and aromatic hydrocarbons C 18 H 18 Select and construct the oil-paper mixture model according to the molecular number ratio of 1:8:1.
[0015] Specifically, performing molecular dynamics simulations on samples in different degradation states includes: The mean square displacement was introduced to describe the degree of particle diffusion, and the change situation of the mean square displacement of cellulose under different degradation conditions was calculated. Based on the mean square displacement of the cellulose model under different degradation conditions, the glass transition temperature of the cellulose model was obtained. The number of hydrogen bonds contained in the cellulose model under different degradation conditions was calculated, and the change in the number of hydrogen bonds under different degradation conditions was counted. The objective of this study is to calculate the elastic modulus matrix of the cellulose-oil paper blend model after degradation, derive the mechanical modulus of the cellulose molecules, and analyze the change rule of the mechanical modulus.
[0016] Insulating paper subjected to deterioration by mechanical force is more susceptible to glass transition, and cellulose chains in the glassy state are more susceptible to deformation. A thermal field can destroy intermolecular hydrogen bonds. The addition of an electric field destroys hydrogen bonds in the later stages of deterioration, but the mechanical field has little effect on the number of hydrogen bonds. The Young's modulus increases in the X direction where a mechanical field is applied compared to when no mechanical field is applied, and decreases in the Y-axis and Z-axis directions perpendicular to the X direction. Effect of the Invention
[0017] This invention provides a method for testing the mechanical properties of insulating oil paper under electrical, thermal and mechanical combined aging conditions, and carries out the following multi-physical field coupling insulating oil paper aging experiments and molecular dynamics-based insulating oil paper aging simulations to study the mechanical properties of converter transformer insulating oil paper under electrical, thermal and mechanical combined aging conditions. First, the invention analyzes the degradation of the macroscopic mechanical properties of the sample through the polymerization degree and tensile strength of the sample after aging, then uses X-ray diffraction spectroscopy and SEM scanning electron microscopy to initially analyze the microscopic mechanism of the degradation of the mechanical properties of the sample, and finally, by combining with the indicators such as the mean square displacement, interaction energy and mechanical modulus of the insulating paper cellulose obtained by molecular dynamics simulation, the degradation mechanism of the mechanical properties of insulating paper under electrical, thermal and mechanical combined aging conditions is clarified, and the relationship between the changes in the macroscopic mechanical properties and the microscopic physical and chemical properties of insulating paper is established, providing a data basis and theoretical support for the prediction of the life of insulating paper, and at the same time providing an effective method for studying the degradation mechanism of transformer oil paper insulation at the atomic level.
[0018] Of course, any product embodying the present invention need not necessarily achieve all of the above advantages simultaneously. [Brief description of the drawings]
[0019] In order to more clearly describe the technical solutions of the embodiments of the present invention, the drawings necessary for describing the embodiments are briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention, and those skilled in the art can obtain other drawings based on these drawings without creative efforts. [Figure 1a] 1 is a schematic diagram of the overall structure of the degradation experiment platform of the present invention; [Figure 1b] FIG. 2 is an AC and DC circuit diagram of the degradation experiment platform of the present invention. [Diagram 2] FIG. 1 is a schematic diagram of the cellulose chain structure of the present invention. [Diagram 3] FIG. 1 is a schematic diagram of the construction process of the cellulose model of the present invention. [Figure 4a] 1 is a schematic diagram of a paraffin C18H38 molecular model structure of the present invention. [Figure 4b] FIG. 1 is a schematic diagram of a cycloalkane C18H32 molecular model structure of the present invention. [Figure 4c] FIG. 1 is a schematic diagram of the aromatic hydrocarbon C18H18 molecular model structure of the present invention. [Diagram 5] FIG. 2 is a schematic diagram of the oil-paper mixing simulation model structure of the present invention. [Figure 6] FIG. 2 is a schematic diagram showing the change over time in polymerization degree under different aging conditions according to the present invention. [Figure 7] FIG. 2 is a schematic diagram of a fitting curve of the change over time of cumulative loss rate according to the present invention. [Figure 8] FIG. 4 is a diagram showing the relationship between tensile force and strain applied to the insulating paper of the present invention. [Figure 9] FIG. 1 is a schematic diagram of a microscopic form of the present invention. [Figure 10a] FIG. 2 is a schematic diagram showing the change in diffraction intensity after deterioration for five days according to the present invention. [Figure 10b] FIG. 2 is a schematic diagram showing the change in diffraction intensity after deterioration for 10 days according to the present invention. [Figure 10c] FIG. 2 is a schematic diagram showing the change in diffraction intensity after deterioration for 15 days according to the present invention. [Figure 11] FIG. 1 is a schematic diagram showing the time course of MSD under T+E conditions of the present invention. [Figure 12] FIG. 1 is a schematic diagram showing the time course of MSD under the T+E+M conditions of the present invention. [Figure 13] FIG. 2 is a structural schematic diagram showing the change in the condensed state of the polymer of the present invention depending on temperature. [Figure 14] FIG. 2 is a schematic diagram showing the change in MSD of cellulose of the present invention with temperature. [Figure 15] FIG. 2 is a schematic diagram of hydrogen bonds within a cellulose model of the present invention. [Figure 16] FIG. 2 is a diagram showing the change in the amount of hydrogen bonds in the cellulose model of the present invention. [Figure 17a] FIG. 2 is a graph showing the change in hydrogen bond length at a temperature of 400 K according to the present invention. [Figure 17b]FIG. 2 is a graph showing the change in hydrogen bond length at a temperature of 600 K according to the present invention. [Figure 17c] FIG. 2 is a graph showing the change in hydrogen bond length at a temperature of 800 K according to the present invention. [Figure 18a] 3 is a schematic diagram of the change in Young's modulus in the X direction with temperature according to the present invention. [Figure 18b] 1 is a schematic diagram of the change in Young's modulus in the Y direction with temperature according to the present invention. [Figure 18c] Schematic diagram of the change in Young's modulus in the Z direction with temperature according to the present invention. [Figure 19] 2 is a flow chart of a testing method of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The technical solutions in the embodiments of the present invention are clearly and completely described below with reference to the drawings of the embodiments of the present invention, but obviously, the described embodiments are only some of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative efforts are included in the scope of protection of the present invention.
[0021] Example 1 Referring to FIG. 1 to FIG. 19, the present invention provides a method for testing mechanical properties of insulating oil paper due to combined electrical, thermal and mechanical deterioration, Building an AC and DC, thermal and mechanical stress combined degradation experiment platform to prepare insulating oil-paper samples with different degradation states; Measure the polymerization degree and tensile strength of the insulating oil paper samples in different aging states to obtain the change rule of mechanical performance after aging, and observe the microscopic morphology diagrams and XRD spectra of the insulating oil paper samples in different aging states to analyze the deterioration cause of mechanical performance; constructing cellulose molecular chains and amorphous unit cells, optimizing the structure, and obtaining a cellulose model; Building an oil-paper mixture model by considering the effect of insulating oil on insulating oil-paper; and performing molecular dynamics simulations on oil-paper samples in different degradation states based on the cellulose model and the oil-paper mixed model to establish a relationship between the degradation of macroscopic mechanical properties and the changes in microscopic physical and chemical properties of the insulating oil-paper.
[0022] (1) Degradation platform and simulation model (1) Construction of a thermal degradation platform under AC and DC electric fields Specifically, the purpose of constructing an AC / DC-thermal-mechanical stress combined degradation experiment platform is to: Construct a high temperature degradation box, In order to apply a constant amplitude vibration to the insulating oil paper, a vibration generator was installed on the base of the high-temperature deterioration box. An AC and DC circuit is constructed, and the DC voltage and the AC voltage are respectively supplied by two transformers, and the DC voltage and the AC voltage are jointly applied to the insulating sleeve at the top of the degradation box; It involves putting the pre-treated insulating oil-papers into different aging tanks respectively, and arranging the aging tanks inside an aging box.
[0023] In order to study the effects of AC and DC combined voltage, high temperature, and mechanical stress inside the converter transformer on the degradation of oil-penetrated insulating paper, an AC and DC combined thermal and mechanical stress degradation experiment platform was designed. As shown in Figure 1, the experimental platform is composed of a high-temperature degradation box, externally connected AC and DC circuits, and a vibration generator.
[0024] In the aging circuit shown in Figure 1, the DC voltage and AC voltage are supplied by two transformers respectively and applied together to the insulating sleeve at the top of the aging box, and the actual applied voltage value is monitored by a voltage divider and an oscilloscope to prevent insulation breakdown. The pre-treated insulating oil paper is placed in different aging tanks respectively, and the aging tanks are placed inside the aging box. When performing the test, the high-voltage side and the ground end are connected to the top sleeve and the right sleeve of the aging box respectively. In order to provide a constant amplitude vibration, a vibration generator is installed on the base of the aging box to simulate the core vibration caused by the DC bias magnetic field under the actual operating conditions of the converter transformer.
[0025] In the present invention, 140°C was selected as the experimental temperature, and accelerated aging tests were performed for each sample from 0 to 360 hours. From this, it can be estimated from experience that when the aging temperature is 140°C, the aging speed is accelerated by 1024 times compared to when the operating temperature is 80°C, and 360 hours corresponds to about 40 years as an actual aging situation. Regarding the selection of the electric field strength, considering that the electric field strength of the insulating oil paper is between 0.3 and 2.8 kV / mm in the actual operation of the ±800 kV converter transformer, in order to accelerate the aging effect, in the present invention, the electric field strength is set to 5 kV / mm, and the ratio of AC voltage to DC voltage is set to 1:1. Since the vibration of the winding of the transformer is mainly concentrated at the fundamental frequency of 100 Hz, in the present invention, 100 Hz is selected as the frequency of the mechanical stress. The vibration amplitude is set to 1 mm.
[0026] (2) Construction of a simulation model The main component of the insulating paper of converter transformers is a cellulose molecule consisting of numerous β-D-glucopyranosyl groups linked by (1-4)-β-glycosidic bonds, the basic repeating unit of which has the chemical formula (CH 10 O5) n (n is the degree of polymerization). Due to the internal rotation effect of the chemical bonds and the presence of hydrogen bonds, the cellulose chain has a conformation with the bond angles and planes of H shown in Figure 2. 4 It formed a C1 chair conformation.
[0027] Research has shown that different degrees of polymerization of cellulose chains have no obvious differences in molecular conformation and physical and chemical properties in molecular dynamics simulations, and many literatures have constructed cellulose chains with a degree of polymerization of 10 to study their physical and chemical properties, insulation performance and mechanical performance, all of which are consistent with actual data. In the present invention, a cellulose chain with a degree of polymerization of 10 is constructed to study the mechanical performance of cellulose chains under multi-field composite degradation. Considering the interaction between multiple molecular chains, the present invention fills each unit cell with two molecular chains, and the average density is 1.5g / cm. 3 The present invention constructs a cellulobiose molecular model and uses it as the basic repeating unit to construct two cellulose molecular chains with a degree of polymerization of 10, and finally, uses the AC module to set the density to 1.5 g / cm. 3 The amorphous unit cell of was constructed and the structure was optimized using the Forcite module. The construction process and model are shown in Figure 3.
[0028] In actual work, the insulating paper of the converter transformer is immersed in high-temperature insulating oil for a long time, and the organic compounds and trace moisture in the insulating oil are very easy to diffuse and form a stable composite material with the cellulose of the insulating paper. Therefore, considering the influence of insulating oil on the physical and chemical properties and mechanical performance of insulating paper, the present invention further constructed an oil-paper mixed model. Currently, most of the insulating oils used in converter transformers are mineral oils composed of hydrocarbons, but due to the complex refining process, it is difficult to measure all the various complex hydrocarbon substances contained in mineral oils. Therefore, the present invention uses the most representative paraffin C 18 H 38 , Cycloalkane C 18 H 32 and aromatic hydrocarbons C 18 H 18 The molecular ratio is 1:8:1, the model is shown in Figure 4, and the mass fraction is shown in the table. Using the Amorphous Cell module, a unit cell with a side length of a cube is constructed, and insulating oil molecules and cellulose molecules are filled in it, and the density is 1.5 g / cm.3 The model diagram is shown in Figure 5.
[0029] In order to make the hole distribution of the model closer to that of the real material and overcome the potential wells between the local minima of the system, the Anneal module was used to perform energy relaxation on the model, and the initial energy of the system reached a minimum value after repeated annealing, and the annealed model more closely matched the actual chair conformation of the cellulose molecule.
[0030] This invention studied the effects of three external factors, temperature, electric field and mechanical field, on the mechanical properties of insulating paper when applied to it. Forcite module and NPT ensemble were used for simulation calculation and analysis of the entire process, and molecular dynamics calculation was performed for 300ps every 50K in the temperature range from 280K to 680K, where the first 160ps was used for system equilibrium, the last 100ps was used for data analysis, and the last 100ps was set to collect molecular dynamics trajectories every 1ps for calculation analysis. The electric field strength was set to 0.01V / A, i.e. 100kV / mm, taking into account the accelerated degradation effect. In all simulation processes, the upgraded COMPASII mechanical field was used, and the Andersen method and the Berendsen method were used to control the temperature and pressure, respectively. The pressure during the simulation was 0.5GPa, the integration algorithm was Velocity Verlt, the electrostatic interaction was Eward, and the van der Waals interaction was Atom based. All simulations were completed by the Forcite module of MS8.0. After the simulation calculation was completed, the analysis was performed using the Analysis module, and some of the data was exported and processed separately.
[0031] (2) Physical and chemical characteristics of oil-paper insulation deterioration (1) Degree of polymerization The degree of polymerization of insulating paper is a basic parameter that characterizes the degree of its deterioration and can intuitively reflect the mechanical strength of insulating paper. In this experiment, the degree of polymerization of insulating paper was measured using a viscosity test method, and the polymerization degree of insulating paper after 60 hours, 116 hours, 180 hours, 240 hours, 300 hours, and 360 hours of combined thermal, electrical, and mechanical deterioration was recorded to obtain the change in the degree of polymerization over time under each deterioration condition, which is shown in Figure 6.
[0032] As can be seen from Figure 6, the degree of polymerization of all the insulating papers before aging is about 1160. With increasing aging time, the degree of polymerization of all samples decreased significantly and eventually became less than 500, indicating that the aging had entered the middle and late stages. The application of AC and DC electric fields has a significant promoting effect on the decrease in the degree of polymerization of the insulating paper, and the decrease in the degree of polymerization of the insulating paper after vibration is more significant than that of the insulating paper aged by AC and DC electric fields, that is, vibration is a more significant factor in promoting the decrease in the degree of polymerization of the insulating paper.
[0033] The main cause of deterioration of insulating paper is the breakage or displacement of the chemical bonds of the cellulose chains that compose the insulating paper, or the destruction of hydrogen bonds and van der Waals forces, under the influence of factors such as temperature, electric field, mechanical stress, and moisture, which is expressed as a decrease in parameters such as the degree of polymerization and tensile strength in terms of macroscopic mechanical properties. Therefore, the cumulative loss rate of the degree of polymerization of cellulose can be fitted using a first-order reaction rate equation.
[0034]
number
[0035] In the formula, ω DP is the cumulative loss rate of polymerization degree (ω DP If ω = 0, DP = DP0 indicates that the insulating paper is not decomposed, and ω DP = 1, DP = 0 means that the insulating paper is completely decomposed);ω * DP ω DP is the maximum value of k, which indicates the rate of decrease in the degree of polymerization of cellulose when the decomposition of the insulating paper is completed. DPrepresents the rate of change in cumulative loss rate.
[0036] The fitting curve of the cumulative loss rate of cellulose polymerization degree is shown in Fig. 7. The parameters and the goodness of fit R 2 are shown in Table 1.
[0037] Table 1. Fitting parameters for cumulative loss of cellulose polymerization degree [Table 1]
[0038] As can be seen from Figure 7 and Table 1, the cumulative loss rate of insulating paper cellulose under thermal-electrical-mechanical aging and thermal-electrical aging shows an increasing trend, and the cumulative loss rate increases faster under thermal-electrical-mechanical aging, and the rate is k DP increased from 0.01418 to 0.05996. This indicates that the application of stress accelerates the deterioration of the insulating paper. The reason for this is presumably that vibration promotes the loosening of the cellulose chain arrangement, causing chain breakage and displacement, resulting in a decrease in the degree of polymerization of cellulose.
[0039] (2) Tensile strength To further study the effect of vibration on insulating paper, tensile strength tests were conducted on insulating paper with and without vibration treatment, and the stress-strain relationship curves of the two types of insulating paper are shown in Figure 8. According to the stress-strain relationship, the elastic modulus and tensile strength of the insulating paper under the action of TE and TEM can be obtained, as shown in Table 2.
[0040] Table 2 Mechanical properties of insulating paper after deterioration [Table 2]
[0041] Observing Figure 8, we can see that the two curves show similar trends of change and are mainly divided into three stages. First stage: The amount of displacement is proportional to the tensile force, and the ratio of the tensile force to the amount of displacement is the stiffness coefficient of the material. The stiffness coefficient of the insulating paper that has been subjected to vibration is significantly lower than that of the insulating paper that has not been subjected to vibration, which means that the insulating paper is more easily deformed by vibration.
[0042] Second stage: The displacement is no longer proportional to the tensile force, and after passing the inflection point, the displacement increases rapidly while the tensile force basically does not change, and this inflection point is the yield point of the material, and this phenomenon is called the material yield phenomenon. After vibration, the insulating paper becomes more easily deformed due to the decrease in its stiffness coefficient, so the yield point is slightly delayed compared to insulating paper that has not been subjected to vibration, that is, the ductility of the insulating paper is improved by vibration.
[0043] Third stage: The displacement and tensile force return to a proportional relationship, and when the displacement exceeds a certain limit, the tensile force rapidly decreases to 0, at which point the material breaks. The tensile force at which the insulating paper subjected to vibration breaks is 300N, and the tensile force at which the insulating paper not subjected to vibration breaks is 410N, indicating that the breaking point of the insulating paper occurs early due to vibration.
[0044] Comprehensively analyzing the above, the insulation paper subjected to vibration has a lower stiffness coefficient, which reduces the insulation paper's ability to resist deformation, and the material has stronger ductility, which means it has a higher yield point.
[0045] However, the destructive effect of vibration on the insulating paper causes the breaking point to occur early, making the insulating paper more susceptible to breaking: vibration reduces the mechanical properties of the insulating paper, increasing the likelihood of decomposition and breaking during the degradation process, and ultimately destroying the insulating structure.
[0046] (3) Microscopic morphology The insulating paper that had been subjected to thermal, electrical and mechanical combined degradation was observed with a SEM scanning electron microscope, and Figure 9 was obtained. The degradation status of the insulating paper can usually be confirmed by the arrangement status, surface smoothness, average width and breakage status of cellulose in the microscopic morphology diagram. As can be seen from Figure 9, the SEM insulating paper of the undegraded insulating paper has a smooth surface, densely arranged fibers, tight connections between fibers, and an average fiber width of about 180 μm, with no obvious branches, voids or breaks. As can be seen from Figure 9, after 120 hours of degradation, the fiber width of the insulating paper was significantly narrowed to about 110 μm, and at the same time, some wrinkles and voids occurred on the cellulose surface. When the degradation time reached 240 hours, as can be seen from Figure 9, the fiber arrangement became sparse, its average width was reduced to about 60 μm / strip, and the width of the thinnest cellulose was only 40 μm, the connection between fibers became loose, the voids at the connection part increased significantly, and the protrusions and wrinkles on the surface became more obvious. After 360 hours of aging, as can be seen from Figure 9, the fiber arrangement is looser, the width is significantly narrower, the average is only about 50 μm, the number of voids has increased significantly compared to before, and multiple cracks on the fibers can be visually observed. In summary, as the aging time progresses, the degradation of the insulating paper cellulose gradually progresses, and the reason is that the molecular force between the cellulose chains is weakened under stress, the arrangement is loosened, and the cellulose main chain is stretched and broken, resulting in the formation of voids and cracks on the fiber surface. This also supports to a certain extent the cause of the decrease in polymerization degree and tensile strength of the insulating paper after aging mentioned above from the perspective of microscopic structure.
[0047] (4) X-ray diffraction spectrum Polymers made of cellulose have amorphous and crystalline regions, and in this invention, the crystal structure of the crystalline region of cellulose and the transformation between the crystalline and amorphous regions are mainly analyzed by X-ray diffraction analysis. The diffraction intensity in the XRD pattern reflects the strength of the diffraction ability of the phase itself and its proportion in the mixture, the position of the diffraction peak is related to the type of crystal and represents the spacing of the diffraction planes, and the half-width and morphology are functions of the crystal size and strain. The XRD analysis results of samples under different degradation conditions are shown in Figure 10.
[0048] The diffraction peaks of the cellulose polymer appear around 2θ=18.5° and 2θ=16°, which are the diffraction peak representing the crystalline region and the "bulge peak" representing the amorphous region, respectively. Figure 10 shows that the heights of the two diffraction peaks decrease with increasing degradation time, and the decrease becomes even greater under thermal-electrical-mechanical degradation conditions.
[0049] The performance parameters of the XRD spectrum were calculated and are shown in Table 2. In Table 2, I am is the diffraction peak intensity of the amorphous region (diffraction intensity around 2θ=16°, θ is the Bragg angle), and I 002 is the diffraction peak intensity of the crystalline region (diffraction intensity around 2θ=18.5°).
[0050] From the table, under thermal-electrical and thermal-electrical-mechanical degradation conditions, I am and I 002 It can be seen that both decrease monotonically with the extension of the aging time. Under different aging times and conditions, the positions of all the diffraction peaks are about 18.5° and 16°, with no obvious changes, indicating that the crystal type of the insulating paper does not change before and after aging. The diffraction intensity decreases with the increase in aging time, which indicates that the crystalline phase content of the cellulose crystalline region decreases with the increase in aging time, and the diffraction peak intensity in TEM is lower than that in TE. This indicates that the crystalline phase content of the cellulose crystals decreases under the action of mechanical force.
[0051] Under the same degradation conditions, the half-width FwHM 002 increased monotonically with the aging time. This is thought to be because the lattice distortion of cellulose and the refinement of crystal blocks progressed with the extension of the aging time, which resulted in an increase in the selective reflection area in the reciprocal space and a broadening of the diffraction peak.
[0052] In Table 2, the relative crystallinity CrI indicates the ratio of the crystalline region to the entire cellulose microfibril having a crystalline region and an amorphous region, and the crystallite size D indicates the size of the crystal grain. They are calculated according to the Segal formula and the Scherrer formula, respectively.
[0053]
number
[0054] Here, D is the average thickness (Å) of the grains in the direction perpendicular to the crystal plane, K is the Scherrer constant, B is the half-width of the diffraction peak, so K=0.89, θ is the Bragg diffraction angle, and γ is the wavelength of the X-rays, which is usually 1.54056 Å.
[0055] According to the fringed micelle structure theory, the crystalline structure of cellulose is composed of regularly arranged crystalline micelle cells and fringed whiskers extending from the unit cells. There is no clear boundary because it is a continuous transition from the highly crystallized ordered region to the completely amorphous disordered region. This allows the crystalline and amorphous regions of cellulose to be converted to each other, and the crystallinity increases and decreases with the aging time. Although the mechanical force promoted the refinement of the crystal grains, the crystallinity of cellulose under TE conditions with the same aging days was significantly higher than that under TEM, which indicates that part of the crystalline region of the insulating paper board subjected to mechanical stress was transformed into an amorphous region. This increases the flexibility of the molecular chains and makes them easier to deform.
[0056] Table 3 XRD parameters [Table 3]
[0057] (3) Molecular Dynamics Study on Degradation of Oil-Paper Insulation (1) Mean square displacement The performance degradation of insulating paper is closely related to the molecular motion of cellulose, and in order to study the effect of the coupling degradation of multi-physical fields on the molecular motion of insulating paper, the present invention introduces the mean square displacement to describe the degree of particle diffusion. The mean square displacement (MSD) is an index that indicates the deviation of the particle position from the reference position after moving over time, and its definition formula is as follows:
[0058]
number
[0059] N represents the total number of atoms calculated, TIFF2025003273000008.tif53 represents the position vector of the atom, and t represents the current instant.
[0060] The larger the MSD value of the system, the more violent the atomic motion in the system, i.e., the less stable the model. In order to investigate the effect of changes in external conditions on the degree of cellulose molecular motion, the present invention calculates the change in MSD of cellulose under multiple conditions, and shows them in Figures 11 and 12. As can be seen from Figures 11 and 12, under the two conditions, the MSDs both increase with increasing temperature, which indicates that the temperature field enhances the motion of cellulose molecules, which is consistent with the thermal motion theorem of molecules. When the temperature field between 300K and 500K is applied, the change in the MSD value of cellulose is not obvious, and the variation range is within 16Å. 2 When the temperature exceeded 600 K, the MSD began to increase significantly with time, with a variation range of up to 36 Å. 2 and 80 Å 2This indicates that there is a high possibility that the cellulose molecules undergo some state transition between 500K and 600K, weakening the intermolecular forces, changing the condensation structure of the polymer, and making it easier for relative displacement between molecular chains to occur. In addition, when the temperature is between 300K and 500K, there is no significant difference in the MSD of the cellulose molecules before and after the application of mechanical force, but when the temperature is between 600K and 800K, the MSD of the cellulose molecules after the application of a mechanical field can reach twice the MSD without the application of a mechanical field, indicating that the effect of mechanical force on the movement of molecular chains increases as the temperature increases. The reason for this is thought to be that the polymer expands with the increase in temperature, increasing the free volume in which the segments can move, and the effect of mechanical force on the movement of molecular chains also increases.
[0061] Glass transition temperature (T g ) is the temperature at which a polymer changes from a glassy state to a highly elastic state, in which the molecules have the ability to move more strongly. Since the glass transition temperature is caused by the movement of molecular chains, the glass transition temperature of cellulose insulating paper can be determined by investigating the change in the movement of molecular chains. The MSD value of the cellulose model at 10ps under each degradation condition was taken as the representative value at that temperature, and a scatter plot was created. Two fitting curves were obtained by fitting the scatter plot, and the point on the horizontal axis corresponding to their intersection is the glass transition temperature. The state of the polymer changes with temperature, and this process is shown in the figure.
[0062] From Figure 13, we can see that the glass transition temperature under the action of T+E is 519.32 K, and the glass transition temperature under the action of T+E+M is 516.86 K. The glass transition temperature of cellulose decreased due to mechanical force. This indicates that insulating paper subjected to the deterioration action of mechanical force is more likely to undergo glass transition, and the cellulose chains in a glassy state are more easily deformed. The glass transition temperature is mainly related to the flexibility of the cellulose chain segment, and the softer the chain segment, the lower the glass transition temperature. This indicates that mechanical force increases the flexibility of the cellulose molecular chain, making the insulating paper more easily deformed.
[0063] (2) Hydrogen bonds The numerous hydroxyl groups and glycosidic bonds in cellulose provided enough oxygen atoms to interact with hydrogen atoms to form hydrogen bonds. The hydrogen bonds in cellulose exist between and within molecules, and their bond energies are about 12-40 kcal / mol, and their bond lengths are about 0.24-0.32 nm, and they have orientation, saturation, and additive properties. Hydrogen bonds have a certain restraining effect on each particle, which can inhibit particle movement and the breaking of chemical bonds. However, the total number of hydrogen bonds is limited, and their ability to restrain particles is equal to the sum of the bond energies, so there is a strong correlation between the hydrogen bond energy and the number and length of hydrogen bonds. The hydrogen bonds in the cellulose model are shown in Figure 18.
[0064] After completing the molecular dynamics simulation calculations under the influence of thermal field, electric-thermal coupling, and electric-thermal coupling for the cellulose model, we obtained the trajectory file of the last 100ps and used a script to calculate the number of hydrogen bonds contained in the cellulose model in each trail file. In order to reduce the error, we took the average of the number of hydrogen bonds in the 100 trail files and statistically obtained the change in the number of hydrogen bonds under different conditions, as shown in Figure 15. From Figure 15, we can see that the higher the temperature, the fewer the number of hydrogen bonds, and the addition of an electric field reduces the number of hydrogen bonds between molecules, and the force field has little effect on the hydrogen bonds. As the temperature increases, the number of hydrogen bonds continues to decrease, which shows that the higher the temperature and the longer the aging time, the lower the bond energy of the hydrogen bonds between molecules inside the insulating paper, the worse the bonds between molecules, and the more violent the molecular movement. This is consistent with the experimental results showing that the decomposition products of the insulating paper increase with aging time and the degree of polymerization decreases with aging time, indicating that the thermal force field can destroy the hydrogen bonds and cause the aging of the insulating paper.
[0065] The hydrogen bonds after the force field effect is applied do not change significantly from those without the force field, which shows that the effect of the force field on the hydrogen bonds is not large. Comparing the change in the amount of hydrogen bonds after the electric field is applied between 300K and 480K, the amount of hydrogen bonds in the cellulose is higher when the electric field is applied than when the electric field is not applied, but the difference is not large. After 500K in the later stage, the amount of hydrogen bonds in the cellulose model drops sharply under the action of the electric field, and it is even lower than the normal state without the electric field. From this, it can be inferred that in the early stage of deterioration, the distance between cellulose molecules is relatively close, and the deterioration does not have a serious impact, but at this time, the intermolecular action force is strong, so the electric field does not play an obvious role. As the deterioration progresses, the degree of intermolecular bonding decreases, and at this time the effect of the electric field force becomes significant, and the number of hydrogen bonds also decreases. This may cause the deterioration effect to become more intense because the electrothermal bond deterioration is not simply a 1+1 cumulative deterioration, but includes a complex and complex mechanism.
[0066] As can be seen from Figure 15, the length of hydrogen bonds increases with increasing temperature, and the proportion of hydrogen bonds longer than 2.0 Å in length gradually increases from 300 K to 800 K. This indicates that under the action of TEM, the proportion of relatively long hydrogen bonds increases with increasing temperature. The bond energy of hydrogen bonds is inversely proportional to their length, and the longer the length, the weaker the bond energy. This indicates that as the strength of the thermal field increases, the bond energy of hydrogen bonds between cellulose weakens and becomes more likely to be broken.
[0067] The change in the number of hydrogen bonds can affect the mechanical performance of polymers. When the hydrogen bonds of cellulose are reduced, the force between cellulose molecules is weakened, and the molecular chains are more easily oriented under external stress, while the flexibility of the cellulose chains increases and the tensile strength decreases. Comprehensive analysis of the above shows that the thermal field destroys the hydrogen bonds between molecules, and the addition of an electric field destroys the hydrogen bonds in the later stage of degradation, but the force field has little effect on the number of hydrogen bonds. Therefore, the thermal field and electric field reduce the tensile strength of cellulose, and orientation occurs more easily under the action of external force.
[0068] (3) Mechanical properties In order to verify the accuracy of the change in tensile strength of the insulating paper after the above-mentioned deterioration and to predict the mechanical elastic modulus of cellulose, the elastic modulus matrix of a cellulose-oil mixed model after deterioration was calculated by molecular dynamics simulation, the mechanical elastic modulus of the cellulose molecules was derived, and the rule of its change was analyzed.
[0069] In mechanics of materials, the stress on a material and the resulting strain are expressed by Hooke's law as follows:
[0070]
number
[0071] C in the formula ij is a sixth-order elastic modulus matrix, and all the mechanical properties of the material can be derived from this matrix. TIFF2025003273000010.tif44 is stress, TIFF2025003273000011.tif43 is distorted.
[0072] The effective bulk modulus (B) and effective shear modulus (C) can be obtained by the RUSS averaging method.
[0073]
number
[0074]
number
[0075] Since the cellulose model is isotropic, the relationship between the elastic moduli can be obtained as follows:
[0076]
number
[0077] Among the elastic moduli, Young's modulus represents the relationship between stress and strain when a material is subjected to tensile stress, and corresponds to the concept of tensile strength. The elastic modulus of a material can accurately represent the strain caused by the material when it is subjected to external stress, and the study of the change rules of the elastic modulus of a material after deterioration is the basis for the evaluation of the deterioration state and life prediction of insulating paper.
[0078] In the present invention, the Young's modulus and the shear modulus were calculated using Mechanical Properties in the Forcite module of MS software, as shown in the figure. From Figure 18, we can see that the Young's modulus in the X direction where a mechanical force field was applied increased compared to when no mechanical force field was applied, but the Young's modulus decreased in the Y and Z directions perpendicular to the X direction. This is because the action of mechanical stress on the X axis causes the molecular chains to be uniaxially oriented, increasing the mechanical elastic modulus of cellulose in the X axis and decreasing the Young's modulus in the Y and Z directions perpendicular to the X direction. This is consistent with the previous experimental fact that the elastic modulus decreases in the direction perpendicular to the applied force.
[0079] Conclusion: The following conclusions have been obtained from the results of the thermal-electrical-mechanical combined degradation experiments carried out according to the present invention, the polymerization degree and tensile strength tests for the aged samples, the X-ray diffraction patterns, the scanning electron micrographs, and the molecular dynamics simulations: 1) Due to the thermal, electrical and mechanical effects, the polymerization degree of the insulating paper decreases after deterioration, and the rate of increase in the cumulative loss rate increases when vibration is applied. The cumulative loss rate of cellulose reaches a steady state faster, which indicates that mechanical vibration can accelerate the deterioration of the mechanical performance of the insulating paper. 2) The rigidity of the insulating paper subjected to vibration decreases, the yield point occurs in advance, and the paper becomes more likely to break than before vibration. This is because the mechanical force destroys the intermolecular forces, the crystallinity decreases, the cellulose becomes oriented, and the tensile strength in the direction perpendicular to the orientation decreases. 3) The thermo-electric-mechanical effects do not change the type of microcrystals, but they do reduce the relative crystallinity and grain size of the insulating paper fibers. At the same time, the thermo-electric-mechanical effects promote fiber refinement and the appearance and development of voids. The occurrence of vibration promotes fiber refinement, branching, and breakage, loosens the cellulose arrangement, and increases and enlarges the voids, promoting the deterioration of the mechanical performance of the insulating paper.
[0080] In the description of this specification, the use of terms such as "one embodiment," "example," "specific example," and the like means that the particular feature, structure, material, or characteristic described in connection with the example or example is included in at least one example or example of the present invention. In this specification, general expressions of the above terms do not necessarily refer to the same example or example. Furthermore, the particular features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more examples or examples.
[0081] The preferred embodiments of the present invention disclosed above are intended only to help explain the present invention. The preferred embodiments are not exhaustively described in all details, nor are the present invention limited to only the specific embodiments described. Obviously, many modifications and variations can be made in accordance with the present specification. These embodiments have been selected and specifically described in the present specification in order to better explain the principles and practical applications of the present invention, so that those skilled in the art to which the present invention pertains can better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Building an AC and DC, thermal and mechanical stress combined aging experiment platform to prepare insulating oil-paper samples with different aging states; Measure the polymerization degree and tensile strength of the insulating oil paper samples in different aging states to obtain the change rule of mechanical performance after aging, and observe the microscopic morphology diagrams and XRD spectra of the insulating oil paper samples in different aging states to analyze the deterioration cause of mechanical performance; constructing cellulose molecular chains and amorphous unit cells, optimizing the structure, and obtaining a cellulose model; Building an oil-paper mixture model by considering the effect of insulating oil on insulating oil-paper; and performing molecular dynamics simulations on oil-paper samples in different degradation states based on a cellulose model and an oil-paper mixed model to establish a relationship between the degradation of the macroscopic mechanical performance of the insulating oil-paper and the changes in the microscopic physical and chemical properties.
2. Specifically, the construction of an AC / DC / thermal / mechanical stress combined degradation experiment platform includes the following: Construct a high temperature degradation box, In order to apply a constant amplitude vibration to the insulating oil paper, a vibration generator was installed on the base of the high-temperature deterioration box. An AC and DC circuit is constructed, and the DC voltage and the AC voltage are respectively supplied by two transformers, and the DC voltage and the AC voltage are jointly applied to the insulating sleeve at the top of the degradation box; The method for testing the mechanical properties of insulating oil paper subjected to combined electrical, thermal and mechanical deterioration as described in claim 1, characterized in that it includes placing the pretreated insulating oil paper in different deterioration tanks respectively, and arranging the deterioration tanks inside an deterioration box.
3. The preparation of insulating oil-paper samples with different deterioration states includes the following: The method for testing the mechanical properties of insulating oil paper for electrical, thermal and mechanical combined deterioration according to claim 1, characterized in that it includes: applying an experimental temperature of 140°C, an electric field strength of 5 kV / mm, an AC / DC voltage ratio of 1:1, a mechanical stress vibration frequency of 100 Hz, a vibration amplitude of 1 mm, and combining different factors among the three external factors of temperature, electric field and mechanical field to the insulating oil paper sample, and carrying out an accelerated deterioration test for 0 to 360 hours on the insulating oil paper sample.
4. The method for testing the mechanical properties of insulating oil paper for electrical, thermal and mechanical combined degradation as claimed in claim 1, characterized in that the polymerization degree of the insulating oil paper sample is measured by a viscosity test method, the cumulative loss rate of cellulose polymerization degree is fitted by a first-order reaction rate equation to obtain the cumulative loss rate of cellulose under the influence of different factors, a tensile strength test is performed on the insulating oil paper sample that has been subjected to vibration treatment and the insulating oil paper sample that has not been subjected to vibration treatment, the stress-strain relationship curves of the two insulating oil paper samples are drawn, and the elastic modulus and tensile strength under the action of different factors are obtained.
5. The method for testing the mechanical properties of insulating oil paper subjected to combined electrical, thermal and mechanical deterioration, as claimed in claim 4, characterized in that the application of AC and DC electric fields has a significant promoting effect on the decrease in the degree of polymerization, and the decrease in the degree of polymerization of the insulating paper after vibration is more significant than that of insulating paper deteriorated by AC and DC electric fields, i.e., vibration is a more significant factor in promoting the decrease in the degree of polymerization of the insulating paper, and the rigidity coefficient of the insulating paper after vibration decreases, making the insulating paper more susceptible to damage, i.e., vibration reduces the mechanical properties of the insulating paper, making it more susceptible to decomposition or damage during the deterioration process, and ultimately destroying the insulating structure.
6. The method for testing the mechanical properties of insulating oil paper for electrical, thermal and mechanical combined deterioration, as described in claim 1, characterized in that as the deterioration time increases, the deterioration of the insulating paper cellulose becomes gradually more severe, because the molecular forces between the cellulose chains weaken under the action of stress, the arrangement becomes loose, and the cellulose main chains are stretched or broken, resulting in voids and cracks on the surface of the fibers, and the cellulose crystals have a reduced content of crystalline phase due to the action of mechanical force, which increases the flexibility of the molecular chains and makes them more susceptible to deformation.
7. A cellulobiose molecular model was constructed and two cellulose molecular chains with a degree of polymerization of 10 were constructed using the cellulobiose molecular model as the basic repeating unit, and a density of 1.5 g / cm was obtained using the AC module. 3 The method for testing the mechanical properties of insulating oil paper subjected to combined electrical, thermal and mechanical deterioration as described in claim 1, characterized in that an amorphous unit cell of the cellulose ester is constructed, and the structure is optimized using the module of Forcite to obtain a cellulose model.
8. Paraffin C in insulating oil 18 H 38 , Cycloalkane C 18 H 32 and aromatic hydrocarbons C 18 H 18 and constructing an oil-paper mixed model according to a molecular ratio of 1:8:
1.
9. Specifically, performing molecular dynamics simulations on samples in different degradation states includes: The mean square displacement was introduced to describe the degree of particle diffusion, and the change situation of the mean square displacement of cellulose under different degradation conditions was calculated. Based on the mean square displacement of the cellulose model under different degradation conditions, the glass transition temperature of the cellulose model was obtained. The number of hydrogen bonds contained in the cellulose model under different degradation conditions was calculated, and the change in the number of hydrogen bonds under different degradation conditions was counted. The method for testing the mechanical properties of insulating oil paper subjected to combined electrical, thermal and mechanical deterioration, as described in claim 1, characterized in that the method comprises calculating the elastic modulus matrix of the cellulose-oil paper mixed model after deterioration, deriving the mechanical elastic modulus of the cellulose molecules, and analyzing the change rule of the mechanical elastic modulus.
10. The method for testing the mechanical properties of insulating oil paper subjected to the combined electrical, thermal and mechanical deterioration as claimed in claim 1, characterized in that insulating paper subjected to deterioration by mechanical force is prone to glass transition, cellulose chains in a glassy state are easily deformed, a thermal field can destroy intermolecular hydrogen bonds, the addition of an electric field destroys hydrogen bonds in the later stage of deterioration, but a mechanical field has little effect on the number of hydrogen bonds, and the Young's modulus increases in the X direction where a mechanical field is applied compared to when no mechanical field is applied, and decreases in the Y-axis direction and Z-axis directions perpendicular to the X direction.
Citation Information
Patent Citations
Oil paper insulated electrothermic aging test and local discharge integrated detection device of transformer
CN101408579A
Aging test device for transformer insulating oil paper and application method
CN110133461A
Method for evaluating aging life of insulating oil paper in oil-immersed transformer
CN110889234A
Rapid test method for cellulose degradation state of insulation paper
CN115452761A
Insulation paper aging on-line detection device based on fiber collection and dispersion characteristic analysis
CN115856545A
Cited By
Insulating oil and insulating paper information tracing method and system for power transformer
CN119720703A
Method for evaluating aging characteristics of oil impregnated paper based on microscopic parameters
CN120180698A
Automatic tuning and calibration method and system for crystal resonator
CN120377861A
Insulating oil aging failure early warning method, device and equipment and storage medium
CN120652088A
Online monitoring system for insulation state of power equipment
CN120870784A